1994
DOI: 10.1007/bf00294509
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural and immunohistochemical identification of perineurial cells connecting proximal and distal stumps of transected peripheral nerves at early stages of regeneration in silicone tubes

Abstract: Perineurial cells are specialized connective tissue cells that form a barrier between endoneurium and epineurium in normal nerves. In the present study, the formation of the perineurium after transection of rat sciatic nerves was investigated. The cord bridging the gap between proximal and distal stumps through silicone tubes was studied 3, 7, 12, 18, and 21 days after surgery using electron microscopy and antibodies against epithelial membrane antigen (EMA), a marker for perineurial cells that has thus far no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…This orientation may be more important for regeneration guidance and growth than the actual ratio or number of axons in these intermediate units. Fibroblasts, perineurial cells, and Schwann cells are all involved in the ''incipient endoneurial restructuring'' of newly regenerated axons into minifascicles (Scaravilli, 1984;Popovic et al, 1994;Weis et al, 1994). Minifascicles tend to accompany axonal regeneration when and where the blood-nerve barrier has been breached (Stang et al, 2005), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This orientation may be more important for regeneration guidance and growth than the actual ratio or number of axons in these intermediate units. Fibroblasts, perineurial cells, and Schwann cells are all involved in the ''incipient endoneurial restructuring'' of newly regenerated axons into minifascicles (Scaravilli, 1984;Popovic et al, 1994;Weis et al, 1994). Minifascicles tend to accompany axonal regeneration when and where the blood-nerve barrier has been breached (Stang et al, 2005), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 58%
“…The new vessels were apparently fragile, leading to several cases with hemorrhage, which would also contribute to an environment that is not supportive of axonal growth. The early presence of erythrocytes has been previously reported (Weis et al, 1994), but would typically be cleared by 21 days postoperative.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…10 and 11 ) also benefits long nerve gap regeneration. According to several reports, perineurial cells are the first cells to reconnect the proximal and distal stumps after the experimental peripheral nerve lesion, and thereby form a guiding structure for re-growing Schwann cells and axons [23][27]. It is therefore possible that the capacity to form perineurium/endoneurium is a major advantage of Sk-MSC transplantation vs. other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first hours following nerve transection and conduit implantation, wound fluid rich in nerve-supporting factors fills from both nerve stumps into the conduit inner lumen. [65][66][67] During this process, the fibrin matrix (derived from plasma precursors) accumulates naturally to form a complete bridge across the chamber gap providing a substrate for cellular migration. 51 The E10-0.5(1K) conduit may encourage the early orientation of regenerating components on its own, as opposed to filling the inner lumen with a synthetic material to act as a longitudinal cable.…”
mentioning
confidence: 99%